Cognitive Decline Assessment: A Review From Medical Imaging Perspective - Dartora, Caroline Machado; Borelli, Wyllians Vendramini; Koole, Michel; Marques da Silva, Ana Maria (Frontiers in Aging Neuroscience, 2021)
Aging is a complex process that involves changes at both molecular and morphological levels. However, our understanding of how aging affects brain anatomy and function is still poor. In addition, numerous biomarkers and imaging markers have been used clinically to study cognitive decline, usually associated with neurodegenerative diseases such as Alzheimer’s disease (AD). However, the path of cognitive decline from healthy aging to a mild cognitive impairment (MCI) stage has been studied only marginally. This review presents different views and aspects of cognitive decline assessment based on the differences between cognitively unimpaired (CU) and cognitive decline. Moreover, we have discussed the relationship between imaging markers and the change in their patterns with aging using neuropsychological tests. Our goal was to delineate how aging has been studied using medical imaging tools and further explore the aging brain and cognitive decline. We found no consensus among the biomarkers to assess the cognitive decline and its relationship with the cognitive decline trajectory. Brain glucose hypometabolism was found to be directly related to aging and indirectly to cognitive decline. In addition, we still need to understand how to quantify an expected hypometabolism during cognitive decline during aging. The Aβ burden should be longitudinally studied to achieve a better consensus on its association with changes in the brain and cognition decline with aging. There exists a lack of standardization of imaging markers, highlighting the need for their further improvement. In conclusion, we argue that there is a lot to investigate cognitive decline, to understand it better, and seek a window for a suitable and effective treatment strategy.